(untitled) (Bangladesh Journal of Otorhinolaryngology, 2021)
Background: Parapharyngeal tumours are rare accounting for 0.5-1.5% of all head neck tumuors. The anatomy of the Parapharyngeal space (PPS) is responsible for a wide variety of tumours arising from PPS. Objective: Evaluation of the strategy for parapharyngeal tumor surgery based on preoperative symptoms, clinical signs, imaging investigations and histopathology. Methodology: This retrospective study was carried out in the Department of Otolaryngology and Head Neck surgery in Bangabandhu Sheikh Mujib Medical University (BSMMU) included 32 patients were underwent surgery for primary parapharyngeal tumors between January 2018 and December 2019. Informed written consent was obtained from the patients prior to their inclusion in the study. In regard to histologic type there were 21 cases salivary gland origin tumors and 11 of neurogenic tumors. The following data were evaluated preoperative symptoms, histological type, surgical approach and complications patients were evaluated following a laboratory investigations. Results: The most common symptoms of these tumors were a neck swelling. Total of 18 tumors were located in the prestyloid and poststyloid space cases were located 10(31.25%) and 4(12.50%) in the pre and poststyloid. Majority 12(37.50%) was found pleomorphic adenomaof deep lobe of parotid gland followed by 6(18.75%) were schwannoma,4(12.50%) were neurofibroma, 3(9.38%) were ectopic salivary gland tumor,2(6.25%) were mucoepidermoid carcinoma, 2(6.25%) were adenocarcinoma. First bite syndrome and lower lip palsy were common post operative complications. Transcervical approach was the most often performed approach in this study (56.25%). Conclusion: Parapharyngeal tumours most often derived from parotid gland. Most of them are non-malignant. Pleomorphic adenoma is the more common. Surgical resection being the main stay of treatment. Tumours of this complex anatomy call for careful preoperative planning and great skill for selecting the right approach and for management with minimal morbidity and recurrence. Bangladesh J Otorhinolaryngol; April 2021; 27(1): 66-72